INOVASI JEMPUT LAYANI PENDERITA TBC (JELITA TBC) DI PUSKESMAS RAMBAH SAMO I KABUPATEN ROKAN HULU - Yogi Arnas; Zulkarnaini Zulkarnaini (Cross-border, 2021)
Health services provided by local governments through puskesmas are basic needs for the community in addition to clothing, food and education. Through public health centers, the government provides health services and facilities to the community in realizing a healthy and prosperous society. One of the puskesmas that provides health services is the Rambah Samo I Health Center, Rokan Hulu Regency. Through JELITA TBC Innovation (Pick up and Serve TB Patients). The purpose of creating JELITA TBC Innovation is the low priority of TB disease prevention and making it easier for the community to get optimal health services. The purpose of this study was to determine the implementation of JELITA TBC innovation at the Rambah Samo I Health Center, Rokan Hulu Regency and identify factors that hindered the implementation of JELITA TBC innovation. This study uses the attribute theory of innovation success by Bugge in Pandi 2020, in which there are six indicators, namely: Governance and innovation, sources of ideas (source of ideas for innovation), innovation culture (innovation culture), objectives , out comes, expense and obstacles (goals, results, costs and obstacles), collecting innovation data for single innovation (collecting innovation data for single innovation). This type of research is a qualitative method with data collection techniques with interviews, observations, and documentation. The results of this study are that existing innovations have not gone well because there are still inhibiting factors in their implementation, namely the lack of socialization from the puskesmas, the lack of human resources at the puskesmas, and being constrained due to the covid-19 pandemic.